Influence of rapidly oscillating inspired O2 and N2 concentrations on pulmonary vascular function and lung fluid balance in healthy adults - Kelley, Eli F.; Carlson, Alex R.; Wentz, Robert J.; Ziegler, Briana L.; Johnson, Bruce D. (Frontiers in Physiology, 2022)
Introduction: Aircrew may experience rapidly oscillating inspired O2/N2 ratios owing to fluctuations in the on-board oxygen delivery systems (OBOG). Recent investigations suggest these oscillations may contribute to the constellation of physiologic events in aircrew of high-performance aircraft. Therefore, the purpose of this study was to determine whether these “operationally-relevant” environmental challenges may cause decrements in measures of pulmonary vascular physiology. Methods: Thirty healthy participants (Age: 29 ± 5 yr) were recruited and assigned to one of the three exposures. Participants were instrumented for physiologic monitoring and underwent baseline cardiopulmonary physiology testing (ground level) consisting of a rebreathe method for quantifying pulmonary blood flow (Qc), pulmonary capillary blood volume (Vc) and alveolar–capillary conductance (Dm). Ultrasound was used to quantify “comet tails” (measure of lung fluid balance). After baseline testing, the participants had two 45min exposures to an altitude of 8,000ft where they breathed from gas mixtures alternating between 80/20 and 30/70 O2/N2 ratios at the required frequency (30s, 60s, or 120s), separated by repeat baseline measure. Immediately and 45min after the second exposure, baseline measures were repeated. Results: We observed no changes in Qc, Dm or Vc during the 60s exposures. In response to the 30s oscillation exposure, there was a significantly reduced Qc and Vc at the post-testing period (P = 0.03). Additionally, exposure to the 120s oscillations resulted in a significant decrease in Vc at the recovery testing period and an increase in the Dm/Vc ratio at both the post and recovery period (P <0.01). Additionally, we observed no changes in the number of comet tails. Conclusions: These data suggest “operationally-relevant” changes in inspired gas concentrations may cause an acute, albeit mild pulmonary vascular derecruitment, reduced distention and/or mild pulmonary-capillary vasoconstriction, without significant changes in lung fluid balance or respiratory gas exchange. The operational relevance remains less clear, particularly in the setting of additional environmental stressors common during flight (e.g., g forces).